Gas explosions of methane-air mixtures in a large-scale tube. (1st February 2021) - Li, Zhan; Chen, Li; Yan, Haichun; Fang, Qin; Zhang, Yadong; Xiang, Hengbo; Liu, Yang; Wang, Senpei
Highlights: Field tests of methane-air explosion in a large-scale tube were conducted. Numerical model of methane-air explosions in the large-scale tube was developed. Effects of concentration and venting configurations on gas explosion loads were discussed. The effect of high-velocity zone on the overpressure distribution was revealed. Abstract: 12 batches of premixed methane-air mixture explosion tests were conducted in a 30 m long testing tube with section dimensions of 0.8 m × 0.8 m to explore the loading characteristics of gas explosion inside the tube. The pressure-time histories and flame travel distance of each test were recorded and analyzed. A 3D numerical model was developed and numerical simulations were carried out by using the open-source Computation Fluid Dynamic (CFD) toolbox OpenFOAM. Based on testing and numerical results, the characteristics of gas explosion loading inside the large-scale tube were revealed. It is found that the existence of vents can reduce the peak pressure by 13%–91% and increase the flame travelling distance inside the tube. The peak pressure increases with the rising concentration when the gas concentration range is 7.5%–9.5% and decreases with the rising concentration when the gas concentration ranges 9.5%–11.5%. End venting can reduce the peak pressure along the tube by 17%–69%. With the decrease of vent number, the gas explosion inside the tube is enhanced and the side vents closed to the ignition can reduce the gas explosion loads inside the tube effectively.